Illness and healing alternatives in Western Europe - Gijswijt-Hofstra, Marijke; Marland, Hilary; Waardt, Hans de (Studies in the social history of medicine., 1997)
The first book to focus on belief, culture and healing in the past; the authors draw on a broad range of material, from studies of demonologists and reports of asylum doctors, to church archives and oral evidence.